Estrogen signaling in the proliferative endometrium: implications in endometriosis - Silva,Rita de Cássia Pereira da Costa e (2016)
SUMMARY Even though the physiological role of estrogen in the female reproductive cycle and endometrial proliferative phase is well established, the signaling pathways by which estrogen exerts its action in the endometrial tissue are still little known. In this regard, advancements in cell culture techniques and maintenance of endometrial cells in cultures enabled the discovery of new signaling mechanisms activated by estrogen in the normal endometrium and in endometriosis. This review aims to present the recent findings in the genomic and non-genomic estrogen signaling pathways in the proliferative human endometrium specifically associated with the pathogenesis and development of endometriosis.